2008
DOI: 10.1016/j.jmatprotec.2007.11.058
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study for optimization of electrical discharge turning (EDT) process

Abstract: Design of experiments Taguchi Electrical discharge turning Material removal rate a b s t r a c t The paper presents the application of the Taguchi robust design methods to optimize the precision and accuracy of the electrical discharge machining process (EDM) for machining of precise cylindrical forms on hard and difficult-to-machine materials. The present study has been carried out on the influence of six design factors: intensity supplied by the generator of the EDM machine (I), pulse-on time (t i ), voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…They also identified that the peak current was the most influential parameter in multi-performance characteristics. Furthermore, an investigation presented [193] the application of Taguchi's robust design to find the optimal machining process parameters of the EDM process of precise cylindrical forms on high-speed steel. The study considered six design factors, namely, intensity supplied by the generator of the EDM machine, pulse-on time, voltage, pulse-off time, servo, and rotational speed, and it evaluated their effect on the MRR.…”
Section: Performance Measures In Edm Of Tool Steelsmentioning
confidence: 99%
“…They also identified that the peak current was the most influential parameter in multi-performance characteristics. Furthermore, an investigation presented [193] the application of Taguchi's robust design to find the optimal machining process parameters of the EDM process of precise cylindrical forms on high-speed steel. The study considered six design factors, namely, intensity supplied by the generator of the EDM machine, pulse-on time, voltage, pulse-off time, servo, and rotational speed, and it evaluated their effect on the MRR.…”
Section: Performance Measures In Edm Of Tool Steelsmentioning
confidence: 99%
“…Normal probability plots have been drawn for both references materials (Fig. 2) and tailings sample larger than 0.05), it can be concluded that normality assumption is valid (Matoorian et al 2008). The homogeneity of variance assumption is verified by plotting residuals versus fitted values, as shown in Figs.…”
Section: Resultsmentioning
confidence: 84%
“…Matoorian et al 102 established optimum process condition for EDT using the Taguchi method. In their investigation, an L 18 orthogonal array, based on the Taguchi design method was adopted to study the effect of process parameter, namely, power, voltage, pulse on-time, rotational speed and servo upon MRR while machining HSS-1.3255.…”
Section: Research In Sinker Edmmentioning
confidence: 99%
“…A cylindrical electrical discharge turned part. 102 obtaining a high MRR in rough machining conditions. This method is recently employed in EDT process.…”
Section: Research In Hybrid Edmmentioning
confidence: 99%